Técnicas de controle para sistemas com saturação - Ferreira, Robson (1999)
One of the most common nonlinear characteristics found in control system practice is the saturation of the plant input signal. Real world all actuators and power supply devices are subject to saturation. When the control signal exceed pre-fixed limits, the analysis and operation based in general on linear models fails, possibly deteriorating performance and sometimes leading to system instability. Another important situation in system control is the switching between controllers acting on a process, this change should be done smoothly and fastly, what is denominated Bumpless transfer action. The consideration of these characteristics lead to the design of special controllers called anti-windup controllers that should maintain stability and performance of the system as if it was always in the linear mode. This dissertation investigates techniques of control for systems with input saturation which maintains closed-loop stability and performance. From the simplest to the most complete scheme.